Study of architectural responses of 3D periodic cellular materials - Cho, Yigil; Ahn, Tae-Hong; Cho, Hoon-Hwe; Shin, Joong-Ho; Moon, Jun Hyuk; Yang, Shu; Choi, In-Suk; Han, Heung Nam; Li, Ju (IOP PUBLISHING LTD, 2013)
The functional properties of periodic cellular solids such as photonic and phononic crystals, nanocrystal superlattices and foams may be tuned by an applied inhomogeneous mechanical strain. A fundamental methodology to analyse the structure of periodic cellular materials is presented here and is compared directly with indentation experiments on three-dimensional microframed polymer photonic crystals. The application of single-continuum-scale finite-element modelling (FEM) was impossible due to the numerous cells involved and the intricate continuum geometry within each cell. However, a method of dual-scale FEM was implemented to provide stress and displacement values on both scales by applying an upper scale continuum FEM with reference to the lower scale continuum FEM to provide coarse-grained stress-strain relationships. Architecture and orientation dependences of the periodic porous materials on the macro-/microscopic responses were investigated under different loading conditions. Our study revealed a computational tool for exploring elastic strain engineering of photonic crystals and, more broadly, may help the design of metamaterials with mechanical controllability.
Keywords: PHOTONIC CRYSTALS; HETEROGENEOUS SOLIDS; PILLAR ARRAYS; ASPECT-RATIO; FABRICATION; MECHANISMS; TEMPLATES; BEHAVIOR